2018
DOI: 10.1186/s12940-018-0409-7
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations of in utero and early life near-roadway air pollution with trajectories of childhood body mass index

Abstract: BackgroundEvidence suggests that childhood near-roadway air pollution (NRAP) exposures contribute to increased body mass index (BMI); however, effects of NRAP exposure during the vulnerable periods including in utero and first year of life have yet to be established. In this study, we examined whether exposure to elevated concentrations of NRAP during in utero and/or first year of life increase childhood BMI growth.MethodsParticipants in the Children’s Health Study enrolled from 2002 to 2003 with annual visits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
67
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 38 publications
1
67
1
Order By: Relevance
“…Fleisch et al found no association between PM 2.5 exposure in the third trimester and BMI z‐scores, skinfold fat, waist circumference, or fat mass in either early (median age 3.3) or mid‐ (median age 7.7) childhood, after adjusting for maternal education. Kim et al found that PM 2.5 exposure was negatively associated with BMI at age 10, for exposure across pregnancy (per 17 parts per billion PM 2.5 change in BMI −0.60 kg/m 2 , 95% CI, −1.10‐0.10) and across the first year of life (per 14.8 parts per billion PM 2.5 change in BMI −0.50 kg/m 2 , 95% CI, −0.90 to −0.02), adjusting for maternal education. Mao et al found positive associations between greater quartiles of exposure to PM 2.5 at preconception (90 days before pregnancy), all three trimesters and an average across trimesters, in regard to the risk of children being affected by overweight or obesity between the ages of 2 and 9 years, adjusting for maternal education and household income.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Fleisch et al found no association between PM 2.5 exposure in the third trimester and BMI z‐scores, skinfold fat, waist circumference, or fat mass in either early (median age 3.3) or mid‐ (median age 7.7) childhood, after adjusting for maternal education. Kim et al found that PM 2.5 exposure was negatively associated with BMI at age 10, for exposure across pregnancy (per 17 parts per billion PM 2.5 change in BMI −0.60 kg/m 2 , 95% CI, −1.10‐0.10) and across the first year of life (per 14.8 parts per billion PM 2.5 change in BMI −0.50 kg/m 2 , 95% CI, −0.90 to −0.02), adjusting for maternal education. Mao et al found positive associations between greater quartiles of exposure to PM 2.5 at preconception (90 days before pregnancy), all three trimesters and an average across trimesters, in regard to the risk of children being affected by overweight or obesity between the ages of 2 and 9 years, adjusting for maternal education and household income.…”
Section: Resultsmentioning
confidence: 99%
“…Two duplicate studies conducted by the same lead authors using the same dataset were identified, one study was retained as environmental measures were included in the fully adjusted model, whereas they were not in the other study. In total, eight studies were included in the narrative synthesis . Four studies were based in the United States, one each in Canada, Denmark, England, and South Korea.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations